3D Finite element simulation of metal waste compaction process - Bokhors, S.; Benhizia, A.; Outtas, T. (University of Eloued جامعة الوادي, 2018)
This paper presents a numerical study of the dynamic compaction of random cylindrical metal waste assembly. The analysis of the process is based on a new method to place the waste randomly in the chamber, using the 3D collision detection function in SolidWorks that can highlight interferences and collisions. The material is considered to be elasto-plastic. A threedimensional study was carried out using the finite element method in an explicit dynamic analysis. The study offer useful information on the packing density variation within the loading applied. The results provide a better understanding of the dynamic compaction process.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Elastoplastic, Random, Waste metal, Compaction